Neuromorphic Digital-Twin-Based Controller for Indoor Multi-UAV Systems Deployment - Reza Ahmadvand; Sarah Safura Sharif; Yaser Mike Banad (IEEE Journal of Indoor and Seamless Positioning and Navigation)
This study introduces a novel distributed cloud-edge framework for autonomous multi-unmanned aerial vehicle (UAV) systems that combines the computational efficiency of neuromorphic computing with nature-inspired control strategies. The proposed architecture equips each UAV with an individual spiking neural network (SNN) that learns to reproduce optimal control signals generated by a cloud-based controller, enabling robust operation even during communication interruptions. By integrating spike coding with nature-inspired control principles inspired by tilapia fish territorial behavior, our system achieves sophisticated formation control and obstacle avoidance in complex urban environments. The distributed architecture leverages cloud computing for complex calculations while maintaining local autonomy through edge-based SNNs, significantly reducing energy consumption and computational overhead compared to traditional centralized approaches. Our framework addresses critical limitations of conventional methods, including the dependence on premodeled environments, computational intensity of traditional methods, and local minima issues in potential field approaches. Simulation results demonstrate the system's effectiveness across two different scenarios: first, the indoor deployment of a multi-UAV system made up of 15 UAVs, and second, the collision-free formation control of a moving UAV flock, including six UAVs considering the obstacle avoidance. Due to the sparsity of spiking patterns, and the event-based nature of SNNs on average for the whole group of UAVs, the framework achieves almost 90% reduction in computational burden compared to traditional von Neumann architectures implementing traditional artificial neural networks.